The Military Organization and Strategies of the Patriots under the Leadership of Dejazmach Belay Zeleke - Chane, Samson (Ethiopian Journal of Social Sciences, 2020)
Ethiopian patriots protested the Italian occupation in different forms from 1936 to 1941. Dejazmach Belay Zeleke was one of the renowned patriot leaderswho could organize tens of thousands of patriots and carried out successful military campaigns against the Italians and their collaborators in some parts of Gojjam, Wollo and Showa. This study explored the military organization and strategies of the patriots under the leadership of Dej. Belay. Primary data were gathered through in-depth and key informant interviews with 17 people.Â Descriptive and interpretive methods were employed to analyse the data. Findings revealed that Belay ensured hierarchical chain of command in the military organization, and assigned chiefs who commanded the patriots in their respective districts. The patriots were organized into five military units as Dereq Tor were well experienced and senior warriors; Yemetreyes Zebegnoch (guards of the machine guns) and Zuriya Safari or Mezezo Tor (rear guards in charge of patrolling the court of Belay and surrounding areas.The Gamme tor or Angach acted as security guards, patrolled military fortifications and nearby villages and took part in military campaigns. The Kemanianishae - literally not less than the other â€“ largely includes young boys organized as guerilla units. Belay organized the council of military advisors responsible to make decisions on military matters. Basically, the patriotsâ€™ military operation was characterized by guerilla fighting and they practiced different military strategies including hit and run, sudden attack, espionage, intercepting and ambushing the enemy, changing sites frequently, encircling camps and strongholds. The military organization and strategies created cohesiveness among the patriots, reduced the magnitude of casualties and contributed to the success of the patriots resistance.